1997
DOI: 10.1016/s0895-7061(96)00350-0
|View full text |Cite
|
Sign up to set email alerts
|

Isosorbide Nitrates, Nitroglycerin, and Sodium Nitroprusside Induce Vasodilation Concomitantly With Inhibition of Carbonic Anhydrase I in Erythrocytes

Abstract: This study describes the relationship between nitroglycerin, isosorbide dinitrate, sodium nitroprusside, and carbonic anhydrase I, as well as the involvement of this carbonic anhydrase I in vasodilation. Two groups of coronary patients and a group of rabbits underwent treatment with the above-mentioned vasodilating drugs. The activity of red blood cell carbonic anhydrase was monitored and determined by the stopped-flow method. The results show that these drugs inhibit the activity of the isozyme in parallel to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Thus, vasoconstrictor compounds act as CA I activators, whereas vasodilating compounds act as CA I inhibitors. Acetazolamide, a CA inhibitor, is also a potent vasodilator 16 and prostaglandins (PG)E 1 , PGE 2 and PGI 2 , NO and organic nitrates are CA inhibitors 17–19 . Indomethacin (a cyclo‐oxygenase inhibitor) activates CA I and acts as an antagonist towards acetazolamide, prostaglandins and NO at the level of this enzyme 20…”
Section: Introductionmentioning
confidence: 99%
“…Thus, vasoconstrictor compounds act as CA I activators, whereas vasodilating compounds act as CA I inhibitors. Acetazolamide, a CA inhibitor, is also a potent vasodilator 16 and prostaglandins (PG)E 1 , PGE 2 and PGI 2 , NO and organic nitrates are CA inhibitors 17–19 . Indomethacin (a cyclo‐oxygenase inhibitor) activates CA I and acts as an antagonist towards acetazolamide, prostaglandins and NO at the level of this enzyme 20…”
Section: Introductionmentioning
confidence: 99%
“…Puscas et al cesses in the organism. In our conception, the pH increase induced by CA I inhibition might influence the binding of hypotensive stimuli to their specific receptors, followed by signal transduction to the cytoplasm of smooth muscle cells with subsequent vasodilating effects (9,14). Similarly, the reduction in pH induced by vascular smooth muscle CA I activation with hypertensive agents may influence the membrane specific receptor and signal transduction in the vascular smooth muscle cytosol, with subsequent vasoconstrictive effects (14).…”
Section: Discussionmentioning
confidence: 99%
“…Our studies have also shown that vasoconstriction is accompanied by carbonic anhydrase I activation, and vasodilation is accompanied by carbonic anhydrase I inhibition. The most used vasoconstrictive therapeutic agents increase carbonic anhydrase I activity, whereas vasodilating drugs reduce the activity of this isozyme 9 , 10 , 11 , 12 , 13…”
mentioning
confidence: 99%